STRATEGI OPTIMALISASI PEMERINTAH INDONESIA DALAM MENINGKATKAN KUALITAS PELAYANAN TRANSPORTASI UMUM - Afandi, Ficky; Khairina, Etika; Dompak, Timbul (Program Studi Administrasi Publik, FISIP, Universitas Tulang Bawang Lampung, 2025)
Transportation infrastructure plays a vital role in supporting mobility and delivery of goods, as well as attracting investment. This study identifies challenges faced, such as congestion caused by rapid growth of motorized vehicles, and low utilization of public transportation due to the quality of service that is considered inadequate. Through a qualitative descriptive approach, data were collected from literature and case studies on the implementation of government strategies, including the Buy the Service (BTS) Scheme, integration of transportation modes, and the use of information technology. The results show that these strategies can improve accessibility and efficiency of transportation, as well as reduce congestion in urban areas. This study recommends the need for long-term planning and collaboration between the central and regional governments to optimize existing resources, so that the quality of public transportation services can improve and meet the mobility needs of the community. Keywords: Government; Public Transportation; Strategy; Service